2020
DOI: 10.2147/dddt.s249162
|View full text |Cite
|
Sign up to set email alerts
|

<p>Astaxanthin Attenuates Neuroinflammation in Status Epilepticus Rats by Regulating the ATP-P2X7R Signal</p>

Abstract: Background: As a life-threatening neurological emergency, status epilepticus (SE) is often refractory to available treatment. Current studies have shown a causal role of neuroinflammation in patients with lower seizure thresholds and driving seizures. The ATP-gated purinergic P2X7 receptor (P2X7R) is mainly expressed on the microglia, which function as gatekeepers of inflammation. Although emerging evidence has demonstrated significant anti-inflammatory effects of astaxanthin (AST) in SE, the associated mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…AST also effectively inhibits the inflammatory response in the rat brain and down-regulates the expression of P2X7R (ATP-gated purinergic receptor). All these suggest that AST dysfunction and energy metabolism may have a synergistic interaction ( Guazzelli et al, 2019 ; Er et al, 2020 ; Wang et al, 2020 ) which in turn affects the ATP-dependent LGP2 and MDA5 to play a synergistic antiviral effect, but the specific mechanism is not clear and further research is needed.…”
Section: Discussionmentioning
confidence: 99%
“…AST also effectively inhibits the inflammatory response in the rat brain and down-regulates the expression of P2X7R (ATP-gated purinergic receptor). All these suggest that AST dysfunction and energy metabolism may have a synergistic interaction ( Guazzelli et al, 2019 ; Er et al, 2020 ; Wang et al, 2020 ) which in turn affects the ATP-dependent LGP2 and MDA5 to play a synergistic antiviral effect, but the specific mechanism is not clear and further research is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, translational work in mice and rats suggest that P2XRs could be novel targets for AED development due to epilepsy promoting the upregulation of P2Y6, P2Y12, P2X4, and P2X7 receptors on activated microglia [326,327] and promote neuroinflammation. Specifically, Wang et al recently showed that usage of the anti-inflammatory drug Astaxanthin can attenuate the P2X7R-mediated neuroinflammation that is associated with status epilepticus (SE) [328]. As outlined above, limited release and rapid degradation limit the amount of ATP in the extracellular milieu of healthy brains.…”
Section: Epilepsymentioning
confidence: 99%
“…In the same model, a recent study reported that oral treatment with an ATX emulsion to increase its bioavailability improved cognitive function and exhibited antiinflammatory activity by down-regulating inflammation-related proteins such as COX-2, iNOS, TNF-α, IL-6, and IL-1β and increasing IL-10 levels [240]. Furthermore, ATX was effective in attenuating status epilepticus-induced neuroinflammation in rats by suppress-ing extracellular ATP levels and the consequent P2X7R inhibition, a microglial receptor involved in inflammation [241]. The neuroprotective effects of this compound were also evidenced in a model of subarachnoid haemorrhage via inhibition of MMP-9 levels and activity [242] and up-regulation of SIRT1 expression [243].…”
Section: In Vivo Studiesmentioning
confidence: 99%